Applying quantile regression to assess the relationship between R&D, technology import and patent performance in Taiwan - Chung-Chu Chuang; Chung-Min Tsai; Hsiao-Chen Chang; Yi-Hsien Wang (Journal of Risk and Financial Management, 2021)
Electronics companies are facing global economic and trade competition. As patents can form an endowment shield that protects the development of corporate capabilities, companies are actively increasing their number of patents and attaching importance to technological research and development and patent management to achieve differentiated strategic effects. As such, patent layout and research and development (R&D) investment have become important strategic weapons for Taiwanese manufacturers, with which to enter the international market or compete among enterprises. This study first utilized the principal components analysis method to define patents in terms of the number of patents and the times patents are cited, with R&D defined in terms of expenditure and intensity. Furthermore, this study used a quantile regression model to visualize the relationship between R&D, technological imports, and patent performance in Taiwanese listed electronics companies. The empirical results show that technological imports in the second time-lag period require patents, while the effect on patents varies alongside industry characteristics. In addition, the empirical results found that the total assets, number of employees, and number of patent inventors are also factors that significantly affect patents. This research proposes that Taiwan's listed electronics companies should expand their scale, increase their economic efficiency, maximize their resources, increase their patents, enhance their corporate value, boost their investor confidence, and improve their industry competitiveness.
Keywords: 330; patent; quantile regression; R&D; technology import